IMPROVING EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AND SELF-EFFICACY MEDIATED BY JOB SATISFACTION - Ayundasari, Dini Yunita; Sudiro, Achmad; Irawanto, Dodi Wirawan (Universitas Brawijaya, Indonesia, 2017)
The research aims to find out whether there is any significant correlation between work motivation and self-efficacy and employee performance, mediated by job satisfaction in Regional Licensing and Investment Agency of East Kalimantan Province. The research method used in this research is a quantitative method. The data was collected using questionnaires and the sampling technique used in this research is saturated-sampling. Population and sample in this research is all employees working in Regional Licensing and Investment Agency of East Kalimantan Province with a total of 77 respondents. Data analysis method used in this research is Partial Least Square (PLS) method, using 3.0 SmartPLS program. The result of the research shows that motivation influences job satisfaction, self-efficacy influences job satisfaction, job satisfaction influences employee performance, self-efficacy influences employee performance, motivation influences employee performance mediated by job satisfaction, and self-efficacy influences employee performance mediated by job satisfaction.